Prevalence and burden of carotid and femoral atherosclerosis in subjects older than 30 years-old without known cardiovascular disease determined by bidimensional vascular ultrasound. (25th November 2020) - Botto, F; Obregon, S; Di Leva, A; Fischer Sohn, G; Bang, J.H; Koretzky, M; Kotliar, C
Abstract: Introduction: 2019 ESC guidelines on dyslipidemia (DLP) and diabetes (DM) recommend (class IIa) measurement of arterial (carotid and/or femoral) plaque burden with vascular ultrasound (VUS) as a risk modifier in individuals at low or moderate risk with DLP and in asymptomatic patients with DM. However, there are no standard thresholds to categorize atherosclerosis burden (AB) measured by 2D-VUS, a simple, safe and spread technology. Purpose: To explore carotid (c) and femoral (f) plaques prevalence and AB according to age, sex and cardiovascular risk factors (CVRF) in subjects older than 30 years-old without known atherosclerotic cardiovascular disease (ASCVD) Methods: Among 9, 987 consecutive individuals self-referred or referred by physicians for a cardiovascular workup, we present a cross-sectional analysis of 5, 775 first visits of those between 30 and 80 years-old without known ASCVD. We registered prospectively information about CVRF, lifestyle and anthropometrics and determined the prevalence of atherosclerotic plaques evaluating bilateral carotid and femoral arteries with 2D-VUS, applying the Mannheim Consensus definition. Further, we estimated c-AB as the sum of all carotid plaque areas (in mm 2 ), and f-AB according to the presence of unilateral, bilateral or no femoral plaques. Median c-AB and 25–75th percentiles by age and sex were determined. We finally examined the association of AB with number of CVRF adjusted by age. Results: 61% were men, mean age was 51.3 (SD 10.6) years. CVRF were hypertension 53.3%, dyslipidemia 50.3%, sedentarism 56.9%, obesity 28.2%, smoking 16.6% and diabetes 7.3%. Near 10% had no CVRF, 23.1% had 1, 29.8% had 2 and 37.4% had ≥3 CVRF. 42% were medicated on antihypertensives and 17.8% on lipid-lowering drugs. Globally, plaque prevalence was 51% in carotid arteries, 39.3% in femoral arteries, 62.4% in carotid or femoral arteries, and 37.6% in neither. There was an age-related increasing pattern in both sex, stepper in men compared to women before 50 years-old (see graph). Median cAB showed also increasing values with aging, starting at 40 years-old and being higher in men than women with nearly 8 to 10 years ahead of time. Likewise it was observed regarding the presence of uni and bilateral femoral plaques. Finally, there was an increasing prevalence of plaques by number of CVRF, higher in men than women, either in the whole population and in those younger than 50 years-old. However, plaques prevalence was elevated in subjects with 0 (44.9% in men and 35.2% in women) or 1 CVRF (59.2% in men and 44.4% in women), leveraged by age. Conclusions: We observed a high prevalence of carotid or femoral atherosclerosis, higher in men than women, and a high AB in both sex, starting before the fourth decade of life and increasing with age. In spite of a significant association to classic CVRF, a significant number of subjects with paucity of CVRF were diagnosed with atherosclerosis Funding Acknowledgement: Type of funding source: None